KAJIAN ANALISIS KINERJA USAHA MIKRO KECIL MENENGAH (UMKM) DENGAN MENGGUNAKAN METODE BALANCE SCORECARD - Edi Wahyu Wibowo (JURNAL LENTERA BISNIS, 2017)
ABSTRACT Micro Small Medium Enterprises (MSMEs) as an organization is required to have a good performance. Performance is becoming a world issue today. This happens as a consequence of the public demand for the need for excellent service or high quality service. Quality is inseparable from the standard, because performance is measured by standards. Through performance, it is expected to demonstrate its professional contribution significantly in improving the quality of service affecting general service to the organization in which it works, and the ultimate impact is on the quality of life and welfare of the community. In order for the performance of MSMEs is good then the measuring tool is needed to know how far the success rate performance of MSMEs itself. One tool to measure performance is to use a balance scorecard. Balance scorecard is a measure of company performance strategy integrated in 4 perspectives that is financial perspective, customer, internal process and learning and growth. Balance scorecard is a management system mechanism capable of translating organizational vision and strategy into real action in the field. Balance Scorecard is one of the management tools that has been proven to help many companies in implementing its business strategy. Balance Scorecard is expected to generate strategic decisions to improve the performance of MSMEs. Balance scorecard will measure in 4 perspectives, namely the financial perspective that is about Increased revenue and cost efficiency. In the customer perspective will be measured on increasing the number of customers and reduce the number of customer complaints. In an internal perspective the process will be analyzed on improving service process time and after-sales service efficiency. In the learning and growth perspective will be analyzed on improving employee skills and retaining employee retention. Keywords : Micro Small Medium Enterprises (MSMEs), Balance Scorecard, Performance